COMPARISON OF FUNCTIONAL PERFORMANCE AND KINESIOPHOBIA BETWEEN BREAST CANCER SURVIVORS AND APPARENTLY HEALTHY WOMEN - Marques, Vitor Alves; Santos, Wanderson dos; Ferreira-Junior, João; Silva, Maria; Silva, Naiany; Alves, Rafael; Noleto, Flavia; Vieiria, Carlos (Mastology, 2026)
Objective: The aim of this study was to compare functional performance and kinesiophobia between breast cancer survivors and apparently healthy women. Methods: In all, 62 women participated the study and they were divided into a control group (CNT) (age: 52.16±7.59) composed of healthy women and breast cancer survivors (SCM) (age: 52.93±8.95). The functional performance was evaluated by the DASH and the kinesiophobia; it was evaluated by the Tampa Scale. The normality of the data was evaluated by the Shapiro-Wilk test. Data were analyzed by the Student’s t-test. The significance level was defined a priori at p<0.05. The unpaired t-test was used to compare functional performance, and the MannWhitney U test was used to compare kinesiophobia. Results: The SCM group showed worse levels of functional performance (p<0.001) and higher levels kinesiophobia than the CNT group (p=0.05). Conclusion: SCM women have low levels of functional performance and higher levels of kinesiophobia.